Longitudinal Change of Clinical and Biological Measures in Early Parkinson's Disease: Parkinson's Progression Markers Initiative Cohort. Issue 5 (23rd March 2018) - Simuni, Tanya; Siderowf, Andrew; Lasch, Shirley; Coffey, Chris S.; Caspell‐Garcia, Chelsea; Jennings, Danna; Tanner, Caroline M.; Trojanowski, John Q.; Shaw, Leslie M.; Seibyl, John; Schuff, Norbert; Singleton, Andrew; et al.
ABSTRACT: Objective: The objective of this study was to assess longitudinal change in clinical and dopamine transporter imaging outcomes in early, untreated PD. Methods: We describe 5‐year longitudinal change of the MDS‐UPDRS and other clinical measures using results from the Parkinson's Progression Markers Initiative, a longitudinal cohort study of early Parkinson's disease (PD) participants untreated at baseline. We also provide data on the longitudinal change in dopamine transporter 123‐I Ioflupane striatal binding and correlation between the 2 measures. Results: A total of 423 PD participants were recruited, and 358 remain in the study at year 5. Baseline MDS‐UPDRS total score was 32.4 (standard deviation 13.1), and the average annual change (assessed medications OFF for the treated participants) was 7.45 (11.6), 3.11 (11.7), 4(11.9), 4.7 (11.1), and 1.74(11.9) for years 1, 2, 3, 4, and 5, respectively ( P < .0001 for the change over time), with a steeper change in year 1. Dopaminergic therapy had a significant effect on the change of MDS‐UPDRS. There was a significant longitudinal change in dopamine transporter binding in all striatal regions ( P < .001). There was a significant but weak correlation between MDS‐UPDRS and dopamine transporter binding at baseline and years 1, 2, and 4, but no correlation between the rate of change of the 2 variables. Conclusions: We present 5‐year longitudinal data on the change of the MDS‐UPDRS and other clinical and dopamine transporter imaging outcome measures in early PD. These data can be used for sample size estimates for interventional studies in the de novo PD population. © 2018 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.